Предмет: Алгебра,
автор: velievadinara
найдите сумму корней уравнения 3x(x-2)=x-4
Ответы
Автор ответа:
0
получается 3x²-6x=x-4
переносим 3x²-6x-x+4=0
3x²-7x+4=0
D= 49-48=1
x1=7-1/6=1
x2=7+1/6=1.3
x1+x2=1+1.3=2.3
переносим 3x²-6x-x+4=0
3x²-7x+4=0
D= 49-48=1
x1=7-1/6=1
x2=7+1/6=1.3
x1+x2=1+1.3=2.3
Автор ответа:
0
3x(x-2)=x-4
3x²-6x=x-4
3x²-6x-x+4=0
3x²-7x+4=0
Д= (-7)²-4*3*4= 49-48=1
x₁= 1,3
x₂= 1
3x²-6x=x-4
3x²-6x-x+4=0
3x²-7x+4=0
Д= (-7)²-4*3*4= 49-48=1
x₁= 1,3
x₂= 1
Похожие вопросы
Предмет: Другие предметы,
автор: bibibibi68
Предмет: Қазақ тiлi,
автор: hahahaha30
Предмет: Физика,
автор: tolstovaolesya2006
Предмет: Математика,
автор: matrix875